1996
DOI: 10.1016/0304-3959(95)00180-8
|View full text |Cite
|
Sign up to set email alerts
|

Direct conversion from oral morphine to transdermal fentanyl: a multicenter study in patients with cancer pain

Abstract: Direct conversion from oral morphine to transdermal fentanyl with a ratio of oral morphine/transdermal fentanyl (100:1 mg) daily was examined in patients with cancer pain. Patients with a 'stable and low level of cancer pain' receiving a constant dosage of sustained release morphine during a pre-study phase of 6 days were included in the study. Initial fentanyl dosage was calculated by a conversion table. The transdermal system was changed every 72 h and the dosage was adjusted to the needs of the patients acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
152
5
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(174 citation statements)
references
References 30 publications
12
152
5
5
Order By: Relevance
“…6 Constipation and drowsiness were the most common limiting adverse effects observed in our study. Constipation and drowsiness were found to be more prominent in morphine group then in fentanyl 6,7,8 group inspite of the fact that we used high dose of fentanyl which was equivalent to 225-314 mg of morphine. Except for the 6 illiterate patient compliance 6 was good in both the groups.…”
Section: Discussionmentioning
confidence: 83%
“…6 Constipation and drowsiness were the most common limiting adverse effects observed in our study. Constipation and drowsiness were found to be more prominent in morphine group then in fentanyl 6,7,8 group inspite of the fact that we used high dose of fentanyl which was equivalent to 225-314 mg of morphine. Except for the 6 illiterate patient compliance 6 was good in both the groups.…”
Section: Discussionmentioning
confidence: 83%
“…In these studies, morphine was reported to develop constipation more frequently or require more laxatives than fentanyl [4][5][6]. The cause of these results was attributed to differences in the distribution of the opioids in blood and brain, depending on the lipid solubility [7].…”
Section: Discussionmentioning
confidence: 99%
“…Third, once the systems are removed, the blood fentanyl concentration does not immediately fall at a rate predicted from intravenous fentanyl pharmacokinetics (3,5). Thus both analgesia and any side effects that may be present will decline gradually after patch removal.…”
Section: Discussionmentioning
confidence: 99%